In the Shadow of the Pandemic: Unearthing Unequal Justice Vis-à-vis Dispute Resolution - Sukhsimranjit Singh (Washington University Journal of Law and Policy, 2022)
The pandemic has not been generous to any of us. It has stolen lives, eaten life savings, broken relationships, and devastated entire families. It has also unearthed the often-unseen power imbalances in human conditioning. In this Essay, Singh explores how the COVID-19 pandemic has unearthed unequal access to dispute resolution opportunities for racial and cultural minorities. The author connects his own research with a larger question: how has the pandemic unearthed deep structural imbalances in access to privilege due to economic inequalities for racial and cultural minorities? We often say that dispute resolution mechanisms—particularly mediation and arbitration—provide access to justice, but this Essay questions that myth in the shadow of the pandemic.
Keywords: COVID-19 Pandemic; Dispute Resolution; Mediation; Arbitration; Structural Racism; Economic Inequalities